HISTORY OF THE CREATION OF THE INTERNATIONAL MIGRATION ORGANIZATION - Скрипник, Олена (SWorldJournal, 2024)
The article examines the history of the creation of the International Organization for Migration. The emergence of international migration as an international process of resettlement of people from one country to another and the creation of the first inte